Financial Analysis of Shipbuilding Business in Lampulo Village, Banda Aceh City - Miyana, Rozatul; Rizwan, Thaib (Universitas Syiah Kuala, 2022)
Statistics from the Ministry of Maritime Affairs and Fisheries (KKP) noted that in 2019 the Aceh region had 29,713 fishing vessels. Fishing vessels are an important means for fishing business. With the production of fishing vessels, there will be a running shipbuilding industry. The shipyard serves as a place for shipbuilding as well as a place to repair damaged ships. Shipbuilding is a capture fisheries support industry that can meet the needs of repairs for fishing vessels that carry out loading and unloading at ports. There are three types of shipyards in Indonesia, namely traditional shipyards, semi-modern shipyards and modern shipyards. Shipbuilding business cannot operate optimally if there is less demand from consumers. One of the shipbuilding business industries in Aceh is in Lampulo Village, Kuta Alam District, Banda Aceh City, which is a shipyard that is still traditional. This study aims to determine the feasibility of a shipyard business located in Lampulo Village, Kuta Alam District, Banda Aceh City. The research method used in this research is to use financial analysis methods consisting of profit, Net Present Value (NPV), Net B/C Ratio, Internal Rate of Return (IRR), Payback Period (PP) and Break Event Point (BEP). Based on the data analysis conducted, it was found that the profit obtained was Rp. 13.746.986.912 over a period of 10 years, the NPV is Rp. 10.479.852.239, Net B/C Ratio of 2.3, IRR of 61%, PP of 1.57 or the rate of return on investment value of less than 3 year and BEP or the break-even point of business which is at point 0. Results This exceeds the business feasibility limit, so it can be concluded that the shipyard business in Lampulo Village, Banda Aceh City is in a feasible condition.Keywords: fishing shipyard, financial analysis, Lampulo